2011
DOI: 10.1177/03946320110240s413
|View full text |Cite
|
Sign up to set email alerts
|

Specific Immunotherapy in Children: The Evidence

Abstract: Specific immunotherapy (SIT) is the only treatment able to not only act on the symptoms of allergy but also act on the causes. At present, SIT may be administered in two forms: subcutaneous (SCIT) and sublingual immunotherapy (SLIT). SCIT represents the standard modality of treatment while SLIT has recently been introduced into clinical practice and today represents an accepted alternative to SCIT. The main advantages of SIT that are lacking with drug treatment are long-lasting clinical effects and alteration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 82 publications
0
25
0
1
Order By: Relevance
“…Only a few cases of anaphylaxis have been reported in children receiving SLIT, although none was found in our review. [52][53][54] One important benefit of SIT specific to children may be the potential to modify the response to allergens at an early stage and thus prevent disease progression. 16,20,21,24,28,31 SIT is currently the only treatment with this potential to modify and prevent progression of disease from allergic rhinitis to asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases of anaphylaxis have been reported in children receiving SLIT, although none was found in our review. [52][53][54] One important benefit of SIT specific to children may be the potential to modify the response to allergens at an early stage and thus prevent disease progression. 16,20,21,24,28,31 SIT is currently the only treatment with this potential to modify and prevent progression of disease from allergic rhinitis to asthma.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that long-term SCIT may alleviate asthma symptoms and reduce the required dose of ICS. Previous studies have demonstrated that subcutaneous injection immunotherapy is effective in the treatment of allergic rhinitis and asthma, which may improve the symptom scores by >40% (1115). A previous study indicated that SCIT treatment may alleviate the clinical symptoms of allergic rhinitis as early as 6 weeks following the initiation of treatment (16).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporine and tacrolimus are useful in steroid resistant cases, with no significant side effects, except for a burning sensation during administration having been reported (Utine, Stern, & Akpek, 2010). While immunotherapy is delivered via subcutaneous injection and sublingual (oral) route, ocular symptoms respond less well than nasal symptoms to sublingual route (La Rosa et al, 2011). Oral cyclosporines are however ineffective in treating ocular h e a l t h s a g e s o n d h e i d 2 2 ( 2 0 1 7 ) 1 1 2 e1 2 2 allergies (Utine et al, 2010).…”
Section: Immunosupressivesmentioning
confidence: 99%